The Read-Aloud Method to Develop Reading Literacy at School’s Educational Park - Endah Wredati Rahayu; Ali Mustadi (Jurnal Prima Edukasia, 2022)
This study aims to improve students' reading literacy through the Read-Aloud method. Students' reading literacy has decreased due to the implementation of Learning-From-Home activities as an effect of the Covid-19 pandemic. Learning in this study was done outdoor that concerned literacy activities in a School’s Education Park. This research used the Classroom Action Research (CAR). The subjects of this study were 18 graders of elementary school. Data were collected through observation, test questions, and documentation. The research instrument consisted of student observation sheets in reading activities, reading performance test items, and documentation guidelines. The data were analyzed following the descriptive qualitative techniques. The results indicated that the implementation of Read-Aloud activities at the Educational Park could improve students' reading literacy, particularly in the aspects of fluency and comprehension. For the reading fluency, the students were able to read fluently in a clear intonation with correct pronunciation and use punctuation marks appropriately. While for the comprehension, the students showed the ability to find the main idea, answer questions based on the reading, and conclude the reading content. The increase in the students' reading literacy was also supported by the assessment results, which climbed from the 'low' to the 'excellent' category.